High-hardness wear-resistant matte ceramic antifouling agent and preparation method thereof

By introducing nano-SiC particles and environmentally friendly film-forming resin into a matte ceramic antifouling agent, combined with titanium dioxide sol and fluorinated acrylate, the problems of insufficient hardness and poor wear resistance of traditional ceramic antifouling agents are solved, achieving high hardness, wear resistance, matte finish and antifouling effect, while improving environmental friendliness.

CN121064685APending Publication Date: 2025-12-05FOSHAN DAXING NEW MATERIAL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511628727.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-07
Publication Date
2025-12-05

AI Technical Summary

Technical Problem

Traditional matte ceramic stain repellents offer limited improvement in hardness and lack sufficient wear resistance. They are prone to scratches with long-term use, affecting aesthetics and lifespan. Furthermore, they struggle to balance a matte finish with stain resistance and may contain harmful substances, thus their environmental friendliness needs improvement.

Method used

Nano-SiC particles are introduced into the matte ceramic antifouling agent for modification. An environmentally friendly film-forming resin, water-based acrylic resin, is used, combined with titanium dioxide sol, fluorinated acrylate and organosilicon-modified polyvinyl alcohol. By controlling the dispersibility and chemical bonding of nano-SiC particles, a reinforcing phase is formed, which improves the hardness and antifouling performance of the coating.

Benefits of technology

It significantly improves the coating's hardness, abrasion resistance, and anti-fouling properties, while maintaining a matte finish and reducing volatile organic compound emissions, achieving a balance between environmental friendliness and functionality.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of ceramic antifouling agents, and mainly relates to a high-hardness wear-resistant matte ceramic antifouling agent and a preparation method thereof. The high-hardness wear-resistant matte ceramic antifouling agent is prepared from the following raw materials in parts by weight: 50 to 60 parts of waterborne acrylic resin, 3 to 5 parts of tetraethoxysilane, 0.5 to 1.5 parts of citric acid, 0.1 to 0.5 part of a catalyst, 0.5 to 3 parts of fluorine-containing acrylate, 1 to 10 parts of polymethyl methacrylate microspheres, 20 to 30 parts of water, 1 to 5 parts of titanium dioxide sol and 1 to 5 parts of organic silicon modified polyvinyl alcohol. The organic silicon modified polyvinyl alcohol is obtained by carrying out modification treatment on polyvinyl alcohol by using KH-570. The high-hardness wear-resistant matte ceramic antifouling agent provided by the invention can be used for carrying out good antifouling treatment on the ceramic surface and enhancing the wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the technical field of ceramic antifouling agents, and mainly to a high-hardness, wear-resistant, matte ceramic antifouling agent and its preparation method. Background Technology

[0002] Ceramic materials, due to their excellent high-temperature resistance, corrosion resistance, high hardness, and chemical stability, are widely used in building decoration, electronic components, medical devices, aerospace, and industrial equipment. However, the porous and high surface energy of ceramic surfaces makes them prone to adsorbing contaminants such as oil, dust, water stains, and microorganisms, leading to surface discoloration, corrosion, or performance degradation. For example, architectural ceramics tend to accumulate dirt after long-term use, affecting their aesthetics; industrial ceramic components are easily corroded by chemical media in harsh environments, shortening their service life. To address this issue, ceramic antifouling agents have emerged. By forming a low-surface-energy, dense, or functionalized protective film on the ceramic surface, they effectively block the adsorption of contaminants while endowing the surface with self-cleaning, antibacterial, and corrosion-resistant properties, becoming a key technology for improving the functionality and durability of ceramic materials.

[0003] Although ceramic antifouling agents have made some progress in protective performance, they still have some drawbacks. For example, traditional matte ceramic antifouling agents have limited hardness improvement and insufficient wear resistance. They are prone to scratches after long-term use, which affects their appearance and service life.

[0004] Therefore, developing a ceramic antifouling agent with high hardness, wear resistance, matte finish, and stain resistance is a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0005] In view of the shortcomings of the prior art, the purpose of this application is to provide a high-hardness, wear-resistant, matte ceramic antifouling agent and its preparation method, which aims to provide good antifouling treatment for ceramic surfaces and enhance wear resistance.

[0006] The technical solution of this application is as follows: A high-hardness, wear-resistant, matte ceramic anti-fouling agent comprises the following raw materials in parts by weight: 50-60 parts waterborne acrylic resin, 3-5 parts tetraethyl orthosilicate, 0.5-1.5 parts citric acid, 0.1-0.5 parts catalyst, 0.5-3 parts fluorinated acrylate, 1-10 parts polymethyl methacrylate microspheres, 20-30 parts water, 1-5 parts titanium dioxide sol, 1-5 parts organosilicon-modified polyvinyl alcohol; The organosilicon-modified polyvinyl alcohol was obtained by modifying polyvinyl alcohol using KH-570.

[0007] The hardness of traditional matte ceramic anti-fouling agents is limited, and the wear resistance is insufficient. Long-term use can easily cause scratches, affecting the appearance and service life. At the same time, it is difficult to balance the matte effect and anti-fouling performance. High anti-fouling performance may sacrifice the matte texture. In addition, traditional anti-fouling agents may contain harmful substances, and environmental protection needs to be improved. How to improve the hardness and wear resistance of matte ceramic anti-fouling agents while maintaining excellent matte effect and anti-fouling performance, and taking into account environmental protection, is a problem to be solved.

[0008] The technical solution of the present application introduces nano-SiC particles into the matte ceramic anti-fouling agent for modification. By controlling the particle size, addition amount and dispersity of nano-SiC, it is uniformly dispersed in the coating to form a reinforcing phase. At the same time, an environmentally friendly film-forming resin, water-based acrylic resin, is used to reduce VOC emissions. In addition, silicone-modified polyvinyl alcohol can further improve the anti-fouling performance.

[0009] Titanium dioxide sol can form a coating with certain hardness and provide certain photocatalytic activity, which can decompose the organic stains on the surface. Fluorine-containing acrylate has very low surface energy, which can significantly improve the hydrophobicity and oleophobicity of the coating, thereby preventing the adhesion of stains. Si-PVA as a binder can firmly bond titanium dioxide sol and fluorine-containing acrylate together and form good bonding with the ceramic matrix.

[0010] The titanium dioxide particles in the titanium dioxide sol can generate free radicals under ultraviolet irradiation, decomposing the organic stains on the surface. The fluorinated alkyl group in the fluorine-containing acrylate can reduce the surface energy of the coating, making it difficult for water and oil stains to adhere. The hydroxyl group in Si-PVA can form hydrogen bonds with the hydroxyl group on the ceramic surface, firmly bonding the coating to the ceramic surface.

[0011] Specifically, in the synergistic cooperation of nano-SiC particles, Si-PVA and acrylate system, firstly, tetraethyl orthosilicate (TEOS) is hydrolyzed under the catalysis of hydrochloric acid to form a silicic acid sol, and citric acid as a carbon source is carbonized at high temperature to generate nano-SiC particles uniformly dispersed in the water-based acrylic resin matrix. This process not only utilizes the excellent film-forming performance of acrylic resin to provide a stable dispersion environment for nano-SiC, but also strengthens the coating structure through the interaction between its polar groups and nano-SiC; at the same time, Si-PVA is prepared by grafting γ-methacryloxypropyltrimethoxysilane (KH-570) onto polyvinyl alcohol (PVA), and the silicone group can react with the hydroxyl group on the ceramic surface to form a Si-O-Si chemical bond, significantly enhancing the bonding force between the coating and the ceramic matrix, while the methacryloxy group in KH-570 copolymerizes with fluorine-containing acrylate, further enhancing the internal bonding force of the coating.

[0012] On this basis, the water-based acrylic resin as the main film-forming material not only contributes to good film-forming performance, but also reduces the surface energy of the coating by the introduction of fluorine-containing acrylic ester, giving the coating excellent hydrophobicity and oleophobicity, effectively preventing stain adhesion. This low surface energy property, combined with the high hardness and wear resistance of nano-SiC particles and the strong adhesion of Si-PVA, improves the overall performance of the coating, significantly enhancing the hardness and wear resistance of the coating, while achieving a balance between matte effect and stain resistance. The use of water-based acrylic resin reduces the emission of volatile organic compounds, meeting environmental protection requirements. The introduction of Si-PVA enhances the adhesion of the coating to the substrate through the stability of the chemical bond, improving the durability of the coating.

[0013] In summary, the close synergy between nano-SiC particles, the introduction of Si-PVA, and the use of fluorine-containing acrylic ester modified acrylic ester system significantly improves the key indicators of the coating, and shows significant anti-fouling and wear-resistant effects on the ceramic surface.

[0014] Further, the preparation method of the organosilicon modified polyvinyl alcohol includes the following steps: Mix the polyvinyl alcohol with water at 95-105°C to form a transparent PVA solution; Cool the transparent PVA solution to 40-45°C, add KH-570 and react for 40-60 minutes; the KH-570: PVA = (0.0001-0.0002) g / g; Add p-toluenesulfonic acid and react at 55-65°C for 4-8 hours; the p-toluenesulfonic acid: PVA = (0.00005-0.0001) g / g; Precipitate with an alcohol solution, filter, and dry to obtain the organosilicon modified polyvinyl alcohol.

[0015] By grafting γ-methacryloxypropyltrimethoxysilane (KH-570) onto the molecular chain of polyvinyl alcohol (PVA), organosilicon groups are introduced. The organosilicon groups can react with the hydroxyl groups on the surface of the ceramic to form Si-O-Si chemical bonds, thereby improving the adhesion of the coating to the ceramic substrate.

[0016] At the same time, the methacryloxy group in KH-570 can copolymerize with fluorine-containing acrylic ester to improve the internal adhesion of the coating.

[0017] Organosilicon modified polyvinyl alcohol (Si-PVA) has good film-forming properties of PVA and good adhesion of organosilicon, which can more effectively connect the coating and the ceramic substrate together, improving the durability of the coating.

[0018] Further, the solid-liquid ratio of the polyvinyl alcohol and the water is 1: (5-15) g / mL.

[0019] Further, the catalyst is concentrated hydrochloric acid.

[0020] Further, the high-hardness wear-resistant matte ceramic antifouling agent further comprises 0.1-3 parts by weight of a wet dispersant and 0.1-2 parts by weight of an antifoaming agent.

[0021] Further, the volume ratio of the alcohol solution to the material during the precipitation is 3:1-5:1.

[0022] The application also provides a preparation method of the high-hardness wear-resistant matte ceramic antifouling agent, comprising the following steps: The tetraethyl orthosilicate, the citric acid, and part of the water are stirred and mixed; The catalyst is added and reacted at low temperature for 20-40 minutes, and then reacted at high temperature for 1-2 hours to obtain nano-SiC particles; The polymethyl methacrylate microspheres, the remaining water, and the nano-SiC particles are stirred and mixed; The fluorine-containing acrylic ester is added and stirred and mixed; The water-based acrylic resin is added and stirred and mixed; The Si-PVA solution is continuously added and mixed; The titanium dioxide sol is added and stirred and mixed; Filtration and aging are performed to obtain the high-hardness wear-resistant matte ceramic antifouling agent.

[0023] Further, the preparation method of the high-hardness wear-resistant matte ceramic antifouling agent comprises the following steps: The tetraethyl orthosilicate, the citric acid, and part of the water are stirred and mixed at 400-600 rpm for 10-20 minutes; The catalyst is added, and reacted at low temperature for 20-40 minutes and at high temperature for 1-2 hours at 400-600 rpm to obtain nano-SiC particles; The polymethyl methacrylate microspheres, the remaining water, and the nano-SiC particles are stirred and mixed at 700-900 rpm for 10-30 minutes; The fluorine-containing acrylic ester is added and stirred and mixed at 400-600 rpm for 5-15 minutes; The water-based acrylic resin is added and stirred and mixed at 200-400 rpm for 20-40 minutes; The Si-PVA solution is continuously added and mixed at 200-400 rpm for 30-60 minutes; The titanium dioxide sol is added and stirred and mixed at 200-400 rpm for 20-40 minutes; Filtering, aging, obtaining the high-hardness wear-resistant matte ceramic antifouling agent.

[0024] Further, when the high-hardness wear-resistant matte ceramic antifouling agent further comprises the wet dispersant and the defoaming agent, the preparation method comprises the following steps: Stirring and mixing the tetraethyl orthosilicate, the citric acid and part of the water; Adding the catalyst and reacting for 20-40 minutes at low temperature, and then reacting for 1-2 hours at high temperature to obtain nano-SiC particles; Stirring and mixing the polymethyl methacrylate microspheres, the remaining water, the nano-SiC particles and the wet dispersant; Stirring and mixing the fluorine-containing acrylic ester and the defoaming agent; Stirring and mixing the water-based acrylic resin; Continuously adding the Si-PVA solution and mixing; Stirring and mixing the titanium dioxide sol; Filtering and aging to obtain the high-hardness wear-resistant matte ceramic antifouling agent.

[0025] Further, the polymethyl methacrylate microspheres, the remaining water, the nano-SiC particles and the wet dispersant are stirred and mixed at 700-900 rpm.

[0026] In the present application, the nano-SiC particles are matched with the Si-PVA and the acrylic ester system to realize the synergistic improvement of hardness, wear resistance, matte effect and antifouling performance.

[0027] Specifically, by controlling the ratio of TEOS and citric acid, the reaction temperature and time, the present application can effectively adjust the particle size, morphology and dispersity of the nano-SiC particles, so that they are more fully matched with the Si-PVA and the acrylic ester system.

[0028] Compared with the prior art, the present application has the following beneficial effects: 1. The nano-SiC particles of the present application are uniformly dispersed in the water-based acrylic resin matrix to construct a high-hardness reinforcing phase. The polar groups of the water-based acrylic resin form chemical bonds with the nano-SiC, and the organic silicon groups in the Si-PVA form Si-O-Si chemical bonds with the surface of the ceramic, thereby constructing a three-dimensional crosslinked network, which effectively improves the bonding strength of the coating and the ceramic matrix.

[0029] 2、The nano-SiC particles of the application form a micro-rough surface in the coating, synergize with the low surface energy of the fluorine-containing acrylate, and effectively realize double stain-proofing of hydrophobic and oleophobic. At the same time, Si-PVA as a dispersant ensures uniform distribution of the nano-SiC particles, avoiding the rise of surface gloss caused by particle agglomeration. The photocatalytic activity of the titanium dioxide sol can decompose organic stains, and the self-cleaning ability of the fluorine-containing segment makes the coating maintain a good stain-proofing effect while maintaining a matte texture.

[0030] 3、The application uses water-based acrylic resin to replace traditional solvent-based resin, effectively reducing VOC emissions and being more green and environmentally friendly. The introduction of Si-PVA enhances the adhesion of the coating through the dual action of hydrogen bonding and chemical bonding, and the C-F bond of the fluorine-containing acrylate gives the coating excellent weather resistance. The stain-proofing agent provided by the application realizes the unity of environmental protection, functionality and economy, and provides key technical support for the green transformation of the ceramic industry. DETAILED DESCRIPTION

[0031] In order to facilitate the understanding of the present application, the present application is illustrated as follows. It should be understood by those skilled in the art that the examples are only to help understand the present application and should not be regarded as specific limitations of the present application.

[0032] The present application provides a high-hardness wear-resistant matte ceramic stain-proofing agent, comprising the following raw materials by weight: 50-60 parts of water-based acrylic resin, 3-5 parts of tetraethyl orthosilicate, 0.5-1.5 parts of citric acid, 0.1-0.5 parts of catalyst, 0.5-3 parts of fluorine-containing acrylate, 1-10 parts of polymethyl methacrylate microspheres, 0.1-3 parts of wet dispersant, 0.1-2 parts of defoaming agent, 20-30 parts of water, 1-5 parts of titanium dioxide sol, and 1-5 parts of silicone-modified polyvinyl alcohol.

[0033] The catalyst is concentrated hydrochloric acid (concentration of 36-38%).

[0034] The preparation method of the silicone-modified polyvinyl alcohol includes the following steps: Step A: Polyvinyl alcohol (PVA) is added to a beaker containing deionized water according to a solid-liquid ratio of 1:(5-15) g / mL. The beaker is placed in a water bath, the water bath temperature is set to 95-105°C, and the stirrer is turned on with a stirring speed of 200-400 rpm. Continue stirring until the PVA is completely dissolved to form a transparent PVA solution.

[0035] The polyvinyl alcohol (PVA) is commercially available, with an alcoholysis degree of 87-89% and a molecular weight of 77000-79000.

[0036] Step B: Cool the material of Step A to 40-45°C.

[0037] Add γ-methacryloxypropyltrimethoxysilane (KH-570) drop by drop under stirring, and react for 40-60 min. KH-570: PVA = (0.0001-0.0002) g / g.

[0038] Step C: Add catalyst p-toluenesulfonic acid, and react at 55-65°C for 4-8 h. p-toluenesulfonic acid: PVA = (0.00005-0.0001) g / g.

[0039] Step D: Precipitate with ethanol, wash with ethanol for several times, filter, and vacuum dry at 60°C with hot air to obtain silicone-modified polyvinyl alcohol (Si-PVA).

[0040] The volume ratio of ethanol to the material in step C is 3:1-5:1 during precipitation.

[0041] In the scheme, a preparation method of high-hardness wear-resistant matte ceramic antifouling agent is also provided, which comprises the following steps: Step 1: Pre-dispersion stage: Add 40-60% of deionized water by mass to a high-speed dispersion machine container with dispersion blades, and start stirring with the speed adjusted to 400-600 rpm.

[0042] Step 2: TEOS and citric acid mixing stage: Add tetraethyl orthosilicate and citric acid to the above solution, and stir at 400-600 rpm for 10-20 min to ensure that TEOS and citric acid are fully mixed.

[0043] Step 3: Catalyst addition stage: Slowly add the catalyst, and stir at 400-600 rpm for 20-40 min to make TEOS hydrolyze to form a silicic acid sol.

[0044] Step 4: Temperature rising reaction stage: Control the stirring speed at 200-400 rpm, and raise the temperature of the material in step 3 to 88-93°C for 2-4 h. Then react at 1400-1450°C for 1-2 h to promote the reaction of the silicic acid sol with the carbon source to generate nano-SiC particles.

[0045] By controlling the ratio of TEOS and citric acid, the reaction temperature and time, the particle size, morphology and dispersity of the nano-SiC particles can be adjusted.

[0046] Step 5: Polymethyl methacrylate microsphere (PMMA microsphere) dispersion stage: Set the stirring speed at 700-900 rpm, slowly add PMMA microspheres, nano-SiC particles and wet dispersant into the remaining water, and stir for 10-30 min to ensure that the PMMA microspheres are uniformly dispersed.

[0047] Step 6: Additive addition stage: Add fluorine-containing acrylate and defoaming agent in turn, stirring speed is 400-600 rpm, stirring for 5-15 minutes, to ensure that the additives are fully mixed and uniform.

[0048] Step 7: Resin addition stage: Slowly add the water-based acrylic resin, the stirring speed is controlled at 200-400 rpm, and stirring for 20-40 minutes to ensure that the resin is fully mixed with each component.

[0049] Step 8: Continue to add Si-PVA solution with stirring speed controlled at 200-400 rpm, to fully mix the fluorine-containing acrylate, water-based acrylic resin and Si-PVA solution, and the mixing time is 30-60 min.

[0050] Step 9: Titanium dioxide sol mixing: Slowly add the titanium dioxide sol, control the drop speed to prevent precipitation. Stirring speed is 200-400 rpm for 20-40 minutes to obtain a uniform mixed sol.

[0051] Step 10: Filtration stage: The material of step 9 is filtered through a 200 mesh filter to remove possible impurities and undispersed particles.

[0052] Step 11: Maturation stage: The material of step 10 is left to stand for 24 hours to eliminate bubbles, fully wet and stabilize each component.

[0053] The application is further illustrated by specific examples.

[0054] Example 1 The application provides a high-hardness wear-resistant matte ceramic anti-fouling agent, which comprises the following raw materials: 55 kg of water-based acrylic resin, 4 kg of tetraethyl orthosilicate, 1 kg of citric acid, 0.2 kg of catalyst, 1.5 kg of fluorine-containing acrylate, 6 kg of polymethyl methacrylate microspheres, 1.5 kg of wetting dispersant, 0.3 kg of defoaming agent, 24 kg of water, 2 kg of titanium dioxide sol, and 3.5 kg of silicone-modified polyvinyl alcohol.

[0055] The catalyst is concentrated hydrochloric acid (concentration is 36%), which is commercially available.

[0056] In this embodiment, the fluorine-containing acrylate is specifically perfluorooctylpropyl acrylate, which is purchased from Hubei Xinyuhong Biomedical Technology Co., Ltd.

[0057] The polymethyl methacrylate microspheres are commercially available, purchased from Shanghai Taoyu International Trade Co., Ltd., and the model is PS50UM-10.

[0058] The wetting dispersant is TEGO Dispers 760S.

[0059] The defoaming agent is TEGO Foamex 810 from Degussa.

[0060] The titanium dioxide sol is commercially available from Hangzhou Jibin New Material Co., Ltd., and the model number is SS-TA05WZ.

[0061] The preparation method of the organic silicon modified polyvinyl alcohol includes the following steps: Step A: Polyvinyl alcohol (PVA) is added to a beaker containing deionized water at a solid-liquid ratio of 1:10 (g / mL). The beaker is placed in a water bath, the water bath temperature is set to 100°C, and the stirrer is turned on at a stirring speed of 300 rpm. Continue stirring until the PVA is completely dissolved to form a transparent PVA solution.

[0062] The polyvinyl alcohol (PVA) is commercially available, with an alcoholysis degree of 87-89% and a molecular weight of 77000-79000.

[0063] Step B: The material of step A is cooled to 42°C.

[0064] Under stirring, γ-methacryloxypropyltrimethoxysilane (KH-570) is slowly added dropwise, and the reaction is carried out for 50 min. KH-570:PVA=0.000159g / g.

[0065] Step C: Add the catalyst p-toluenesulfonic acid and react at 60°C for 6 hours. p-toluenesulfonic acid:PVA=0.000065g / g.

[0066] Step D: Precipitate with ethanol and wash several times with ethanol, filter, and vacuum dry at 60°C to obtain the organic silicon modified polyvinyl alcohol (Si-PVA).

[0067] When precipitating, the volume ratio of ethanol to the material of step C is 4:1.

[0068] In the present application, a preparation method of a high-hardness wear-resistant matte ceramic antifouling agent is also provided, which includes the following steps: Step 1: Pre-dispersion stage: 50% of deionized water by mass is added to a high-speed disperser container with a dispersion blade, and the stirring speed is adjusted to 500 rpm.

[0069] Step 2: TEOS and citric acid mixing stage: tetraethyl orthosilicate and citric acid are added to the above solution, and stirred at 500 rpm for 15 minutes to ensure that TEOS and citric acid are fully mixed.

[0070] Step 3: Catalyst addition stage: slowly add the catalyst, and stir at 500 rpm for 30 minutes to make TEOS hydrolyze to form a silica sol.

[0071] Step 4: Temperature reaction stage: The material of step 3 is heated to 90℃ at a stirring speed of 300 rpm for 3 hours. Then it is reacted at 1400℃ for 1.5 hours to promote the reaction of silica sol and carbon source, and in-situ generate nano-SiC particles.

[0072] Step 5: PMMA microsphere dispersion stage: PMMA microspheres, nano-SiC particles, and wet dispersant are slowly added to the remaining water while stirring at a speed of 800 rpm for 20 minutes to ensure uniform dispersion of the PMMA microspheres.

[0073] Step 6: Additive addition stage: Fluorine-containing acrylate and defoaming agent are added in sequence at a stirring speed of 500 rpm for 10 minutes to ensure thorough mixing of the additives.

[0074] Step 7: Resin addition stage: Water-based acrylic resin is slowly added while stirring at a speed of 300 rpm for 30 minutes to ensure thorough mixing of the resin with all components.

[0075] Step 8: Continue to add Si-PVA solution at a stirring speed of 300 rpm to thoroughly mix the fluorine-containing acrylate, water-based acrylic resin, and Si-PVA solution for 40 minutes.

[0076] Step 9: Titanium dioxide sol mixing: Slowly add titanium dioxide sol while controlling the drop speed to prevent precipitation. Stir at a speed of 300 rpm for 30 minutes to obtain a uniform mixed sol.

[0077] Step 10: Filtration stage: Filter the material of step 9 through a 200-mesh filter to remove impurities and undispersed particles that may be present.

[0078] Step 11: Maturation stage: Let the material of step 10 stand for 24 hours to eliminate bubbles and allow the components to fully wet and stabilize.

[0079] The prepared high-hardness wear-resistant matte ceramic stain-resistant agent is applied to the pretreated ceramic surface using a doctor blade method. The coating thickness is controlled at 12 μm. After coating, the ceramic sample is placed in a fume hood and dried at room temperature (25℃) for 24 hours to allow the solvent to evaporate. Then, the ceramic sample is placed in an oven, pre-cured at 80℃ for 1 hour, and finally cured at 150℃ for 30 minutes at a heating rate of 5℃ / min to obtain a ceramic stain-resistant coating.

[0080] The ceramic stain-resistant coating is subjected to the following performance tests: 1. Hardness test: Test according to GB / T 6739-2006 "Paints and Varnishes - Pencil Hardness of Paint Films".

[0081] Test results: 4H 2. Abrasion resistance test: The test was conducted using a TABER abrasion tester, and the test standard was based on GB / T 1768-2006 "Determination of Abrasion Resistance of Paint Film - Sanding Wheel Method".

[0082] A CS-17 grinding wheel was used, with a load of 500 g and a number of revolutions of 500. The weight loss of the coating before and after abrasion was measured.

[0083] The test results showed a weight loss of 5 mg.

[0084] 3. Gloss test: The test was conducted using a gloss meter, and the test standard was based on GB / T 9754-2007 "Determination of 20°, 60° and 85° Specular Gloss of Paint Films - Non-Metallic Pigment Coatings".

[0085] The test angle was 60°.

[0086] The test results showed a gloss of 15 GU.

[0087] 4. Stain resistance test: The test was conducted using the drop method. Ink, coffee, soy sauce, and other stains were dropped onto the coating surface, and after 24 hours of standing, the stains were wiped off with a wet cloth. The removal of the stains was observed.

[0088] The test results showed that the ink, coffee, and soy sauce stains were easily removed without any residue.

[0089] 5. Adhesion test: The test was conducted using the crosshatch method, and the test standard was based on GB / T 9286-1998 "Crosshatch Test for Paint and Varnish Films". A hundred small squares were drawn on the coating surface using a crosshatch knife, and then adhesive tape was applied and peeled off. The coating was observed for any peeling.

[0090] The test results showed a rating of 0, indicating that the coating had good adhesion and no peeling.

[0091] 6. Weather resistance test: The test was conducted using an ultraviolet light accelerated aging test chamber, and the test standard was based on GB / T 16422.3-2014 "Plastics - Laboratory Light Source Exposure Methods - Part 3: Fluorescent UV Lamp". A UVA-340 lamp was used, with an irradiance intensity of 0.76 W / m 2 , and a cycle period of 8 hours of UV irradiation (60°C) and 4 hours of dark condensation (50°C), with a total test time of 500 hours. After the test, the coating surface was observed for any discoloration or cracking.

[0092] The test results showed that the coating surface had no significant discoloration or cracking.

[0093] Comparative Example 1 A commercially available ceramic anti-fouling agent A was used as Comparative Example 1, and the same method as in Example 1 was used to coat the ceramic surface, form an anti-fouling layer, and perform testing.

[0094] Test results: 1. Hardness test: 2H.

[0095] 2. Abrasion resistance test: weight loss was 10 mg.

[0096] 3. Gloss test: 20 GU.

[0097] 4. Anti-fouling performance test: the ink, coffee, and soy sauce stains could not be completely removed and some residues remained.

[0098] 5. Adhesion test: Grade 1 (some squares were detached).

[0099] 6. Weather resistance test: the coating surface appeared slight discoloration and a small amount of fine cracks.

[0100] Comparative Example 2 Comparative Example 2 differed from Example 1 in that the silicone-modified polyvinyl alcohol was replaced with polyvinyl alcohol.

[0101] The polyvinyl alcohol (PVA) was commercially available, with an alcoholysis degree of 87-89% and a molecular weight of 77,000-79,000.

[0102] The same method as in Example 1 was used to coat the ceramic surface, form an anti-fouling layer, and perform testing.

[0103] Test results: 1. Hardness test: H.

[0104] 2. Abrasion resistance test: weight loss was 25 mg.

[0105] 3. Anti-fouling performance test: the ink, coffee, and soy sauce stains could not be completely removed and some residues remained.

[0106] 4. Adhesion test: Grade 1 (some squares were detached).

[0107] 5. Weather resistance test: the coating surface appeared slight discoloration and fine cracks.

[0108] Comparative Example 3 Comparative Example 3 differed from Example 1 in that 4 kg of tetraethyl orthosilicate and 1 kg of citric acid were replaced with 5 kg of commercially available nano-SiC particles, and the catalyst was omitted.

[0109] In this comparative example, the nano-SiC particles were purchased from Hangzhou Jixin New Material Co., Ltd., with an average particle size (D50) of 500 nm.

[0110] The method for preparing the ceramic antifouling agent comprises the following steps: Step 1: Pre-dispersion stage: Deionized water is added to the high-speed disperser container with a dispersion blade, the stirring is started, and the rotation speed is adjusted to 500 rpm. Wetting dispersant is added, and stirring is performed for 10 minutes to ensure that the wetting dispersant is completely dissolved.

[0111] Step 2: Keep the rotation speed, add commercially available nano-SiC particles, and stir for 45 min.

[0112] Step 3: Polymethyl methacrylate microsphere (PMMA microsphere) dispersion stage: The stirring speed is adjusted to 800 rpm, PMMA microspheres are slowly added, and stirring is performed for 20 minutes to ensure uniform dispersion of the PMMA microspheres.

[0113] Step 4: Additive addition stage: Fluorine-containing acrylate and defoaming agent are added in sequence, the stirring speed is 500 rpm, and stirring is performed for 10 minutes to ensure that the additives are fully mixed and uniform.

[0114] Step 5: Resin addition stage: Slowly add the water-based acrylic resin, control the stirring speed at 300 rpm, and stir for 30 minutes to ensure that the resin is fully mixed and uniform with each component.

[0115] Step 6: Temperature rising reaction stage: The stirring speed is controlled at 300 rpm, the material of step 6 is heated to 90℃, and maintained for 3 hours.

[0116] Step 7: Continue to add Si-PVA solution with stirring speed of 300 rpm, so that the fluorine-containing acrylate, water-based acrylic resin and Si-PVA solution are fully mixed, and the mixing time is 30-60 min.

[0117] Step 8: Titanium dioxide sol mixing: Slowly add the titanium dioxide sol, control the dropping speed to prevent precipitation. Stir at 300 rpm for 30 minutes to obtain a uniform mixed sol.

[0118] Step 9: Filtration stage: The material of step 9 is filtered through a 200-mesh filter to remove possible impurities and undispersed particles.

[0119] Step 10: Maturation stage: The material of step 10 is left to stand for 24 hours to eliminate bubbles, fully wet and stabilize each component.

[0120] Coating on the ceramic surface, forming an antifouling layer, and testing in the same way as Example 1.

[0121] Test results: 1. Hardness test: 3H.

[0122] 2. Abrasion resistance test: Weight loss is 12 mg.

[0123] 3. Stain resistance test: The ink, coffee, soy sauce and other stains cannot be completely removed, and there is some residual.

[0124] 4. Adhesion test: Grade 1 (some squares have fallen off).

[0125] 5. Weather resistance test: The coating surface appears slightly discolored and has a small amount of fine cracks.

[0126] In summary, according to the test results of Comparative Examples 1-3 and Example 1, the anti-staining agent provided in Example 1 can provide good matte effect, good wear resistance, good stain resistance, and good weather resistance to the ceramic.

[0127] The commercially available Comparative Example 1 and the Comparative Examples 2-3 prepared by destroying the in-situ generated SiC, Si-PVA and the synergistic cooperation of the acrylate system are obviously not as good as the effect of Example 1 in performance testing.

[0128] It should be understood that the application of the present application is not limited to the above examples, and those skilled in the art can make improvements or changes according to the above description, and all these improvements and changes shall belong to the protection scope of the present application.

Claims

1. A high hardness, wear resistant, matte ceramic stain repellent, characterized in that, The high-hardness wear-resistant matte ceramic antifouling agent comprises the following raw materials by weight: 50-60 parts of water-based acrylic resin, 3-5 parts of tetraethyl orthosilicate, 0.5-1.5 parts of citric acid, 0.1-0.5 parts of catalyst, 0.5-3 parts of fluorine-containing acrylic ester, 1-10 parts of polymethyl methacrylate microspheres, 20-30 parts of water, 1-5 parts of titanium dioxide sol, and 1-5 parts of silicone-modified polyvinyl alcohol. The silicone-modified polyvinyl alcohol is obtained by modifying polyvinyl alcohol with KH-570.

2. The high hardness, wear resistant, matte, ceramic stain resist of claim 1, wherein, The preparation method of the silicone-modified polyvinyl alcohol comprises the following steps: The polyvinyl alcohol is mixed with water at 95-105 ℃ to form a transparent PVA solution. The transparent PVA solution is cooled to 40-45 ℃, and the KH-570 is added and reacted for 40-60 min; the KH-570:PVA = (0.0001-0.0002) g / g. p-Toluenesulfonic acid is added and reacted at 55-65 ℃ for 4-8 hours; the p-toluenesulfonic acid:PVA = (0.00005-0.0001) g / g. The silicone-modified polyvinyl alcohol is obtained by precipitation with an alcohol solution, filtration, and drying.

3. The high hardness, wear resistant, matte, ceramic stain resist of claim 2, wherein, The solid-liquid ratio of the polyvinyl alcohol to the water is 1:(5-15) g / mL.

4. The high hardness, wear resistant, matte, ceramic stain resist of claim 1, wherein, The catalyst is concentrated hydrochloric acid.

5. The high hardness, wear resistant, matte, ceramic stain resist of claim 1, wherein, The high-hardness wear-resistant matte ceramic antifouling agent further comprises 0.1-3 parts by weight of a wetting dispersant and 0.1-2 parts by weight of an antifoaming agent.

6. A method for preparing the high-hardness wear-resistant matte ceramic antifouling agent according to any one of claims 1-5, characterized in that, The method comprises the following steps: The tetraethyl orthosilicate, the citric acid, and part of the water are stirred and mixed; The catalyst is added and reacted at low temperature for 20-40 min, and then reacted at high temperature for 1-2 h to obtain nano-SiC particles; The polymethyl methacrylate microspheres, the remaining water, and the nano-SiC particles are stirred and mixed; The fluorine-containing acrylic ester is added and stirred and mixed; The water-based acrylic resin is added and stirred and mixed; The silicone-modified polyvinyl alcohol is continuously added and mixed; The titanium dioxide sol is added and stirred and mixed; The high-hardness wear-resistant matte ceramic antifouling agent is obtained by filtration and aging.

7. The preparation method of the high-hardness, wear-resistant, matte ceramic antifouling agent according to claim 6, characterized in that, The method comprises the following steps: The tetraethyl orthosilicate, the citric acid, and part of the water are stirred and mixed at 400-600 rpm for 10-20 min; The catalyst is added and reacted at low temperature for 20-40 min and at high temperature for 1-2 h at 400-600 rpm to obtain nano-SiC particles; The polymethyl methacrylate microspheres, the remaining water, and the nano-SiC particles are stirred and mixed at 700-900 rpm for 10-30 min; The fluorine-containing acrylic ester is added and stirred and mixed at 400-600 rpm for 5-15 min; The water-based acrylic resin is added and stirred and mixed at 200-400 rpm for 20-40 min; The silicone-modified polyvinyl alcohol is continuously added and mixed at 200-400 rpm for 30-60 min; The titanium dioxide sol is added and stirred and mixed at 200-400 rpm for 20-40 min; The high-hardness wear-resistant matte ceramic antifouling agent is obtained by filtration and aging.

8. The preparation method of the high-hardness, wear-resistant, matte ceramic antifouling agent according to claim 6, characterized in that, When the high-hardness wear-resistant matte ceramic antifouling agent further comprises a wetting dispersant and a defoaming agent, the preparation method comprises the following steps: Stirring and mixing the tetraethyl orthosilicate, the citric acid and part of the water; Adding the catalyst and reacting at low temperature for 20-40 minutes, and then reacting at high temperature for 1-2 hours to obtain nano-SiC particles; Stirring and mixing the polymethyl methacrylate microspheres, the remaining water, the nano-SiC particles and the wetting dispersant; Stirring and mixing the fluorine-containing acrylic ester and the defoaming agent; Stirring and mixing the water-based acrylic resin; Continuously stirring and mixing the organosilicon modified polyvinyl alcohol; Stirring and mixing the titanium dioxide sol; Filtering and aging to obtain the high-hardness wear-resistant matte ceramic antifouling agent.

9. The preparation method of the high-hardness, wear-resistant, matte ceramic antifouling agent according to claim 8, characterized in that, Stirring and mixing the polymethyl methacrylate microspheres, the remaining water, the nano-SiC particles and the wetting dispersant at 700-900 rpm.

Citation Information

Cited By

  • High-wear-resistance ceramic antifouling agent and preparation method thereof

    CN122233816A